BKM's Criterion of Weak Solutions for the 3D Boussinesq Equations (Journal of Partial Differential Equations, 2014)
" In this present paper, we investigate the Cauchy problem for 3D incompressible Boussinesq equations and establish the Beale-Kato-Majda regularity criterion of smooth solutions in terms of the velocity field in the homogeneous BMO space."
Keywords: Incompressible Boussinesq equations; BKM's criterion; smooth solutions